Education Through Video and Booklet Media Increases Knowledge and Skills of Breastfeeding and Infant Growth and Development in Mother and Toddler Classes - Hasmia Naningsi; Endah Saraswati; Kartini (Jurnal Penelitian Pendidikan IPA, 2025)
The effectiveness of health education using video and booklet media in enhancing breastfeeding knowledge and skills as well as infant growth and development in mother and toddler classes was the main focus of this study. This study was motivated by the importance of nutrition education in improving mothers' understanding of good breastfeeding practices and their impact on child health. Quantitative methods were used, with a comparative analysis of knowledge and skills before and after the educational intervention. Data showed that participants who received the video and booklet intervention experienced a significant increase in breastfeeding knowledge (p < 0.001), compared to the group that did not receive the media. The analysis indicated that the use of both types of media simultaneously was most effective in improving knowledge and skills, with the highest N-Gain score recorded in the group that received both media. Furthermore, the positive influence of audiovisual media in the learning process confirms that a multimodal approach can address various learning styles, promoting better information retention. The results of this study provide valuable insights for developing more effective health education methods in the community, particularly in supporting mothers in breastfeeding and childcare practices.